Thermophilic fungi to dominate aflatoxigenic/mycotoxigenic fungi on food under globalwarming - Paterson, R. Russell M. (2017)
Certain filamentous fungi produce mycotoxins that contaminate food. Mycotoxin contamination of crops is highly influenced by environmental conditions and is already affected by global warming, where there is a succession of mycotoxigenic fungi towards those that have higher optimal growth temperatures. Aflatoxigenic fungi are at the highest limit of temperature although predicted increases in temperature are beyond that constraint. The present paper discusses what will succeed these fungi and represents the first such consideration. Aflatoxins are the most important mycotoxins and are common in tropical produce, much of which is exported to temperate regions. Hot countries may produce safer food under climate change because aflatoxigenic fungi will be inhibited. The same situation will occur in previously temperate regions where these fungi have recently appeared, although decades later. Existing thermotolerant and thermophilic fungi (TTF) will dominate, in contrast to the conventional mycotoxigenic fungi adapting or mutating, as it will be quicker. TTF produce a range of secondary metabolites, or potential mycotoxins and patulin which may become a new threat. In addition, Aspergillus fumigatus will appear more frequently, a serious human pathogen, because it is (a) thermotolerant and (b) present on crops: hence this is an even greater problem. An incubation temperature of 41 ºC needs employing forthwith to detect TTF. Finally, TTF in crops requires study because of the potential for diseases in humans and animals under climate change.